Experimental Investigations of Effect of Sulphur on Beach Sand–Fly Ash–Asphalt (S-F-A) Paving Mixes - Satyakumar, M.; Satheeshchandran, R. (Civil Engineering Dimension, 2013)
The main components of the flexible pavements are asphalt and aggregates. But in most of the places in India there is shortage of the good quality aggregates (especially coarse aggregates), at the same time beach sand is available in plenty in many regions. Due to relative abundance of beach sand, the studies on the utilities of the beach sand in paving mixes are worth taking up. But beach Sand-Asphalt mix alone is not suitable for pavement construction, because of its low stability and high air voids. In the present study, Sand-Fly ash-Asphalt-Sulphur (S-F-A-S) mixes are being made in different proportions and tested for their properties. Fatigue strength, stability, water sensitivity, stiffness modulus and dynamic modulus tests are carried out at standard test conditions and the results are analyzed for drawing conclusions. This study investigates the potential use of abundant ingredients, which may replace the ones which are scarce in nature.